Assessment of inflammatory biomarkers and risk factors for cardiovascular diseases in overweight and obesity - I. T. Murkamilov; K. A. Aitbaev; V. V. Fomin; Zh. A. Murkamilova; Z. F. Yusupova; T. F. Yusupova; F. A. Yusupov (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To study biomarkers of inflammation in overweight and obese individuals.Material and methods. A total of 180 people with overweight or obesity were included. Anthropometric and biochemical parameters were determined in all patients. The concentrations of C-reactive protein (CRP), fibrinogen, interleukin (IL)-6, IL-10, and tumor necrosis factor alpha (TNF-α) were studied.Results. The following significant correlations have been established: IL-6 — with the levels of central aortic pressure, systolic and diastolic blood pressure (BP), heart rate (HR), levels of glucose, uric acid, low-density lipoprotein cholesterol (LDL-C); TNF-α — with concentrations of uric acid, triglycerides, cystatin C, creatinine and glomerular filtration rate; CRP — with body mass index, diastolic BP, heart rate, levels of uric acid, LDL-C, cystatin C. A significant correlation of IL-6, IL-10 and TNF-α with the proteinuria level was established.Conclusion. In individuals with overweight or obesity, a direct correlation was found between serum concentrations of IL-6 and levels of BP, heart rate, lipids, carbohydrates, uric acid and proteinuria. In overweight or obesity, the serum TNF-α level has a direct correlation with hyperuricemia, hyperfibrinogenemia, hypertriglyceridemia, proteinuria and reduced renal filtration function, and the level of CRP is associated with an increase in diastolic BP, heart rate, uric acid, fibrinogen, LDL-C and cystatin C.